Adoptive cell therapy using PD-1+ myeloma-reactive T cells eliminates established myeloma in mice. Issue 1 (20th June 2017) - Jing, Weiqing; Gershan, Jill A.; Blitzer, Grace C.; Palen, Katie; Weber, James; McOlash, Laura; Riese, Matthew; Johnson, Bryon D.
Abstract : Background: Adoptive cellular therapy (ACT) with cancer antigen-reactive T cells following lymphodepletive pre-conditioning has emerged as a potentially curative therapy for patients with advanced cancers. However, identification and enrichment of appropriate T cell subsets for cancer eradication remains a major challenge for hematologic cancers. Methods: PD-1 + and PD-1 − T cell subsets from myeloma-bearing mice were sorted and analyzed for myeloma reactivity in vitro. In addition, the T cells were activated and expanded in culture and given to syngeneic myeloma-bearing mice as ACT. Results: Myeloma-reactive T cells were enriched in the PD-1 + cell subset. Similar results were also observed in a mouse AML model. PD-1 + T cells from myeloma-bearing mice were found to be functional, they could be activated and expanded ex vivo, and they maintained their anti-myeloma reactivity after expansion. Adoptive transfer of ex vivo-expanded PD-1 + T cells together with a PD-L1 blocking antibody eliminated established myeloma in Rag-deficient mice. Both CD8 and CD4 T cell subsets were important for eradicating myeloma. Adoptively transferred PD-1 + T cells persisted in recipient mice and were able to mount an adaptive memory immune response. Conclusions: These results demonstrate that PD-1 is a biomarker for functional myeloma-specific T cells, and that activated and expanded PD-1 + T cells can be effective as ACT for myeloma. Furthermore, this strategy could be useful for treating other hematologic cancers.